Hubungan Stres Akibat Kerja dengan Kelelahan Kerja pada Pengemudi Mobil Tangki Integrated Terminal Surabaya - Ayu Adela Miartama; Dani Nasirul Haqi; Siti Arum Alia (Universitas Airlangga, 2023)
Background: Many industrial locations have been observed to have a high prevalence of work fatigue, which poses health and safety issues. Driving can be tiring, especially if the body is not rested so it can increase the risk of accidents. Accidents to tank car drivers can be fatal because they can cause massive losses to the company. Subjective work fatigue can be induced by various factors, such as work-related stress. Objectives: The purpose of this research was to analyze the relationship between work-related stress with work fatigue on the tank car driver of the PT Pertamina Patra Niaga and the fatigue and stress management that should be carried out. Methods: This research was an observational analytic conducted on a sample of 205 tank car drivers. The dependent variable in this research was subjective work fatigue. Data analysis using Spearman Correlation test. Results: The Spearman correlation coefficient was 0.071, which means that the variables of work-related stress and subjective work fatigue did not have a significant relationship. Conclusion: Variable work-related stress was not related to work fatigue may occur because other variables were not analyzed so it did not show a description of the causes of fatigue experienced. Companies must perform driver intervention programs to prevent stress and fatigue from worsening.